Enhancing higher education curricula: A case study from the University of Waikato, New Zealand. (17th July 2018) - Longhurst, Robyn; Jones, Alister
Abstract : In 2014, the University of Waikato launched the Curriculum Enhancement Programme (CEP). As the leaders of this programme we have used auto-ethnography to reflect critically on our experience. Throughout the course of the CEP some things have gone well; others, in hindsight, have not gone so well and in retrospect we would have done them differently. This includes using more channels of communication, more frequently, especially with staff; getting all of Waikato's faculties to pull together more effectively as one institution; and working harder to increase students' opportunities for interdisciplinarity in teaching and research. These lessons, we hope, will be helpful for others also embarking on wide-scale curriculum change.